Agouti-related protein neuron circuits that regulate appetite - Sternson, Scott M.; Atasoy, Deniz (Karger, 2014)
New tools for mapping and manipulating molecularly defined neural circuits have improved the understanding of how the central nervous system regulates appetite. Studies that focused on Agouti-related protein neurons, a starvation-sensitive hypothalamic population, have identified multiple circuit elements that can elicit or suppress feeding behavior. Distinct axon projections of this neuron population point to different circuits that regulate long-term appetite, short-term feeding, or visceral malaise-mediated anorexia. Here, we review recent studies examining these neural circuits that control food intake.
WOS: 000348622800002
PubMed ID: 25402352
Keywords: Agouti-Related Protein; Appetite; Ghrelin